2014
DOI: 10.34068/joe.52.02.18
|View full text |Cite
|
Sign up to set email alerts
|

Doing the Work of Extension: Three Approaches to Identify, Amplify, and Implement Outreach

Abstract: This article explores the literature and practice of how the Cooperative Extension Service does its work and asks if traditional outreach and engagement models have room for innovative delivery mechanisms that may identify emerging trends and help meet community needs. It considers three innovative approaches to the educational mission: sense-making, contextual (typological) framing, and an internal starting with why concept. It discusses how each might offer processes that would help Extension workers identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This also means that Extension was not ranked among the top three sources by 47% of respondents, illustrating that sports field managers’ views of helpful information sources for annual bluegrass were highly varied. Studies have found that urban populations traditionally have low awareness of Extension (Fox et al 2017; Henning et al 2014; Raison 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This also means that Extension was not ranked among the top three sources by 47% of respondents, illustrating that sports field managers’ views of helpful information sources for annual bluegrass were highly varied. Studies have found that urban populations traditionally have low awareness of Extension (Fox et al 2017; Henning et al 2014; Raison 2014).…”
Section: Resultsmentioning
confidence: 99%
“…As such, the lack of Extension presence may diminish its impact. This lack of on-call expertise is one of several documented challenges to Extension delivery in urban settings (Collins and Gaolach 2018; Fox et al 2017; Gaolach et al 2017; Henning et al 2014; Raison 2014).…”
Section: Resultsmentioning
confidence: 99%
“…To increase civic engagement and contribute to meaningful community development, communities require significant human and social capital [54,55]. The Cooperative Extension Service has four categories related to programming outreach: Agriculture and Natural Resources, 4-H Youth Development, Family and Consumer Sciences, and Community Development [56]. However, within Georgia, the extension system does not have personnel specifically designated to provide programs and outreach specifically related to Community Development [57].…”
Section: Civic Engagement and Community Developmentmentioning
confidence: 99%